Building socialism, constructing people : identity patterns and stereotypes in late 1940s and 1950s Romanian cultural press /: identity patterns and stereotypes in late 1940s and 1950s Romanian cultural press. (2015) - Fâtu-Tutoveanu, Andrada
No abstract available